Monody-based Compositions: José Evangelista’s Clos de vie and Alap & Gat - Tan, Zihua (Circuit, 2017)
José Evangelista’s Clos de vie (1983) and Alap & Gat (1998) are comparable in two ways: the compositional thinking behind the works was informed by his study on gamelan music and North Indian music, respectively, and most of the music materials stem from a long monody. In the former piece, he uses a 170-note long monody as a springboard to create a series of textures—“near unison,” “phase-shifted,” “complex,” and “complete unison.” These textures, together with a quotation from Claude Vivier’s Lonely Child, delineate each section of the piece. Another monody, which is 88 notes long, is used to generate pitch materials for different structure-bearing motives in the second work, either in its entirety or in a fragmented manner. The forms of this work were modeled after two types of North Indian compositions—“Alap” and “Gat.”